LEGAL PROTECTION FOR VICTIMS IN AGREEMENT ON ONLINE LOAN SHARKS PRACTICE IN INDONESIA - Surahmi, Mila; Junaidi, Junaidi; Rafie, Patih Ahmad (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2020)
Indonesia's economic growth is currently experiencing tidal economic growth. During this pandemic, Indonesia's economic conditions have become very unstable. One means to improve the social economy in a country is by providing loans from official financial institutions in the form of money or capital to people in need. However, in practice, this situation used by unscrupulous persons (loan sharks) to obtain a large profit, by providing funds/capital for people who need it with a simple and easy condition, but requiring high interest and high risk and adversely affect society when unable to fulfill a required agreement. Nowadays the practice of loan sharks in the community has evolved considerably along with the development or advancement of technology. The former borrower must meet directly with the lender (loan sharks). Now the practice of the moneylenders already "online" the emergence of financial services based on digital technology or financial technology (fintech). The problem arising from the practice of Loan Sharks has been very much in the midst of Indonesian society, such as acts of harassment / unlawful acts in billing to borrowers. Of course, the presence of the country needed to provide legal certainty to achieve order and justice in society. Therefore, this research focuses highlights on the validity of the agreement that is the basis of the legal relationship between borrowers and the lender; The legal consequences of such agreement; and legal protection for victims in agreement on the practice of online loan sharks in Indonesia. The research used is normative juridical research, with a statutory approach and a conceptual approach. This research can be known criteria of a valid agreement so that can be determined legal protection efforts that can be given to victims due to the agreement on the practice of online loan sharks.